High-damping and conducting epoxy nanocomposite using both zinc oxide particles and carbon nanofibers - Jae-Soon Jang; Gyo Woo Lee; Hyung-ick Kim; Sung Yong Hong; Lijie Ci; Jae-Do Nam; Jonghwan Suhr (Journal of Materiomics, 2018)
In this study, high-damping and conducting epoxy nanocomposites were developed with carbon nanofibers as conducting materials, and zinc oxide particles as piezoelectric materials. The mechanical and electrical properties, electrical impedance, and loss factors were investigated by uniaxial tensile tests, voltage measurement, impedance measurement, and 3-point bending tests. Two percolation thresholds were found: the percolation threshold of resistivity due to the carbon nanofibers forming conductive networks in the matrix; and the impedance threshold due to the zinc oxide particles acting like electric barriers. A poling treatment of the high-damping and conducting epoxy nanocomposite was considered, and we found that poling treatment helped to make the networks more conductive and to generate voltage from ZnO particles. A high-damping and conducting epoxy nanocomposite with 3 wt% CNF and 10 wt% ZnO exhibited higher loss factor than those of others tested. Keywords: Damping, Piezoelectric materials, Impedance, Poling treatment, Loss factor